2013
DOI: 10.1098/rsta.2012.0429
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of light-molecule endofullerenes

Abstract: Molecular endofullerenes are supramolecular systems consisting of fullerene cages encapsulating small molecules. Although most early examples consist of encapsulated metal clusters, recently developed synthetic routes have provided endofullerenes with non-metallic guest molecules in high purity and macroscopic quantities. The encapsulated light molecule behaves as a confined quantum rotor, displaying rotational quantization as well as translational quantization, and a rich coupling between the translational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
64
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 103 publications
0
64
0
1
Order By: Relevance
“…Good yields with cage filling factors approaching 100 per cent have now provided samples in sufficient volume to make inelastic neutron scattering (INS) experiments a practical reality, thus enabling the quantum dynamics of the entrapped molecule to be studied in detail. Alongside nuclear magnetic resonance (NMR) [5][6][7] and infrared (IR) spectroscopy [8][9][10][11], INS is one of a range of experimental techniques that have been employed in recent years to investigate the quantum rotation and translation of the confined molecules. Previous INS studies have been conducted on the model complex H 2 @C 60 [11,12] and its isotopomer HD@C 60 [11,13] which have highly symmetric confining potentials, as well as H 2 @ATOCF [14] which is an open-cage derivative with an anisotropic cage potential.…”
Section: Introductionmentioning
confidence: 99%
“…Good yields with cage filling factors approaching 100 per cent have now provided samples in sufficient volume to make inelastic neutron scattering (INS) experiments a practical reality, thus enabling the quantum dynamics of the entrapped molecule to be studied in detail. Alongside nuclear magnetic resonance (NMR) [5][6][7] and infrared (IR) spectroscopy [8][9][10][11], INS is one of a range of experimental techniques that have been employed in recent years to investigate the quantum rotation and translation of the confined molecules. Previous INS studies have been conducted on the model complex H 2 @C 60 [11,12] and its isotopomer HD@C 60 [11,13] which have highly symmetric confining potentials, as well as H 2 @ATOCF [14] which is an open-cage derivative with an anisotropic cage potential.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The inert and highly symmetric, three-dimensionale nvironmentoft he cavity,means that enclosed (endohedral) species are expectedt ob ehave much as they would in the very low pressure gas state, with preservation of free rotationd own to cryogenic temperatures. [2] Although direct synthesis of endohedral metallofullerenes, [3] and fullerenes containing individual atoms (nobleg as@C 60 [4] and the remarkable N@C 60 [5] )i s possible in very low yield, currently the only high-yielding route to small molecule endofullerenes is via the process of "moleculars urgery" [6] wherebyc hemical transformationsa re used to open ah ole in the fullerene, am olecule is inserted, and af urthers eries of reactions is then used to suture the openinga nd reform the pristine fullerenes hell. To date, this has only been achieved for the incorporation of H 2 , [7] H 2 O [8] and HF, [9] as well as their related isotopologues.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Them acroscopic quantities of endohedral fullerenes provided by molecular surgery have allowed detailed investigation of physical properties,i ncluding by neutron scattering, infrared spectroscopy,a nd NMR spectroscopy. [19] These methods have shown that, as ar esult of the inert and highly symmetrical environment of the cavity,a ne ntrapped molecule behaves much as would be expected in the very lowpressure gas state, [17,[19][20][21][22][23] displaying free rotation at cryogenic temperatures. [19][20][21][22][23][24] The16-membered orifice of 2 is too small to allow entry of bigger guests,b ut these can be accommodated by the larger (17-membered) opening of fullerene 3.…”
mentioning
confidence: 99%
“…[19] These methods have shown that, as ar esult of the inert and highly symmetrical environment of the cavity,a ne ntrapped molecule behaves much as would be expected in the very lowpressure gas state, [17,[19][20][21][22][23] displaying free rotation at cryogenic temperatures. [19][20][21][22][23][24] The16-membered orifice of 2 is too small to allow entry of bigger guests,b ut these can be accommodated by the larger (17-membered) opening of fullerene 3. [25] Insertion of N 2 and CO 2 , [26] CH 3 OH and H 2 CO, [27] CH 4 and NH 3 , [28] NO, [29] and O 2 , [30] into 3 have all been recently described, but aprocedure for suturing the opening of A@3 to give A@C 60 has not yet been reported.…”
mentioning
confidence: 99%